Improving Marital Harmony for Husband-Wife of Different Cultures in the Early Marriage Years - Fabiola Hendrati (Institute of Research and Community Service, University of Brawijaya)
The purpose of this research is to create a model program to improve the marital conjugal harmony of different cultures (Flores husband - Javanese wife) with an age range of 1-10 years of marriage which is the age range of marriage prone to divorce. Participants in this study were members of Flobamora who married women from the Javanese, so the participants are married couples of different cultures to the age of 1-10 years of marriage. This study was an experimental study-kuasi Locally-particular. The experimental group will receive treatment Enneagram Modified Program in each weekend (Saturday-Sunday) for approximately 6 weeks, while the control group remained participate week-end program, but not given treatment Enneagram Modified Program. Data analysis technique used is the Mixed-Anova or Anava A mix B.